The Suma De Geographia By Fernández De Enciso, 1519: Piloting and Geography (Global Journal of Human-Social Science, 2023)
In this article we delve into the text of Mart n Fern ndez de Enciso from a global perspective after analyzing the general aspects the specific contents methods of astronomical positioning descriptive geography the adaptation of the text to teaching and the modernity band framed in the formation of the pilots of the Carrera de Indias of the time slot in which it edited As a result the Suma de Geographia is a manual for the pilots of the Carrera de Indias made up of the three subjects necessary for the pilot of the time astronomy navigation and geography
Keywords: martín fernández de enciso: piloting; geography; navigation; century xvi